Dynamic governance : embedding culture, capabilities and change in Singapore - Neo, Boon Siong (World Scientific, 2007)
This book provides an in-depth look at dynamic governance, the key to success in a world of rapid, increasing globalization and unrelenting technological advancements. If bureaucratic public institutions can evolve and embed the culture and capabilities that enable continuous learning and change, their contributions to a country's socio-economic progress and prosperity would be enormous. The lessons from their efforts in institutionalizing culture, capabilities and change could provide meaningful and valuable insights for transforming organizations in other contexts.